Zoobenthos and sediments time series in southern Königshafen, Sylt, Germany, 2003 to 2012 - Werner Armonies (PANGAEA, 2022)
In supplement to an ongoing zoobenthos and sediments time series in the subtidal of List Reede, the adjoining intertidal area was sampled 46 times between September 2003 and June 2012. During that period, the same 12 sites were analysed for macrozoobenthos and granulometric sediment composition, always contemporaneous as possible to subtidal sampling dates. The resulting data set was deemed to enable comparisons of subtidal and intertidal variability of sediment and community composition.